Strategic Planning Practices and their Impact on Activating Financial Governance in Public Organizations: An Applied Study on Telecom Egypt - Elwakel, Manal Mohamed Ahmed (The Arab Journal of Administration, 2025)
The study aimed to examine strategic planning practices and their impact on activating financial governance in public organizations, an applied study on the Telecom Egypt, and by trying to answer the main question of the study and the sub-questions of the research problem, and based on the theoretical analytical descriptive approach of the previous literature in this field through four hypotheses It was researched, and it became clear from the results of the study that there is a relationship between the practices of strategic planning management in terms of analyzing the internal environment and financial governance in terms of rationalizing expenditures, in addition to the existence of a relationship between the practices of analyzing the external environment and financial integrity, practices of setting strategic vision and the sustainability of financial resources, practices of setting strategic goals. Financial transparency, and the validity of the four hypotheses. Among the most important recommendations of the study is the development of a clear strategy for the authority based on the four strategic planning practices, in addition to strengthening financial governance practices and standards in all its dimensions and following up their implementation in accordance with the authority’s strategic plan.